Restructuring of Insolvent Corporations in Canada - Krüger, Josef GA (Potchefstroom Electronic Law Journal, 2017)
This paper gives a very general outline of the formal restructuring of insolvent corporations in Canada. For a South African audience, it is important to understand that in Canada a distinction is made between an "insolvent person" and a "bankrupt". A "bankrupt" means a person who has made an assignment into bankruptcy (voluntarily), or against whom a bankruptcy order has been made. An "insolvent person" means a person who is not bankrupt and who resides, carries on business or has property in Canada, whose liabilities to creditors amount to 1 000, and who is for any reason unable to meet his obligations as they generally become due, or who has ceased to pay his current obligations in the ordinary course of business as they generally become due, or the aggregate of whose property is not, at a fair valuation, sufficient, or, if disposed of at a fairly conducted sale under legal process would not be sufficient to enable payment of all his obligations, due and accruing due. An "insolvent person" in Canada may avoid bankruptcy by resorting to restructuring processes created by statute. The fact that a person becomes insolvent does not necessarily spell bankruptcy. Canadians are fortunate to have access to bankruptcy courts and insolvency practitioners with a high level of commercial and legal skills to assist them in restructuring their financial affairs and avoiding bankruptcy.